Intertextual transactions in American and Irish fictions By Andrzej Kopcewicz - Ambroży-Lis, Paulina (Studia Anglica Posnaniensia, 2011)
Review. Intertextual transactions in American and Irish fictions By Andrzej Kopcewicz